Lipid droplets are formed in 2-cell-like cells - Asuka FURUTA; Toshinobu NAKAMURA (The Society for Reproduction and Development, 2021)
Embryonic stem (ES) cells, derived from the inner cell mass of a blastocyst, are believed to pluripotent cells and give rise to embryonic, but not extraembryonic, tissues. In mice, totipotent 2-cell stage embryo-like (2-cell-like) cells, which are identified by reactivation of murine endogenous retrovirus with leucin transfer RNA primer (MuERV-L), arise at a very few frequencies in ES cell cultures. Here, we found that a lipid droplet forms during the transition from ES cells to 2-cell-like cells, and we propose that 2-cell-like cells utilize a unique energy storage and production pathway.